Effet imprévu d’un traité : Lausanne a changé la cuisine grecque ! - Joëlle Dalègre (Cahiers Balkaniques)
Abstract: Lausanne 1923. More than one million two hundred thousand people from the former Ottoman Empire had to leave their lands forever and settle in Greece. They carry with them their culture, and in this culture, their cuisine, which is much richer and more varied than that of the Kingdom of Greece. This heritage definitely transformed Greek cuisine, even if today it is simultaneously exalted, invoked and… distorted.